Zone-wise investigation of creep behaviour 9Cr–1Mo steel weld joints. Issue 2 (22nd January 2019) - Yadav, Surya D.; Vasantharaja, P.; Riedlsperger, Florian; Nagaraju, S.; Vasudevan, M.
ABSTRACT: Distinct regions such as weld metal, heat-affected zone (HAZ) and base metal of P9 steel weld joints fabricated by various welding processes were investigated using impression creep testing. Smaller prior austenitic grain size, lower density of precipitates and dislocations resulted in faster recovery and higher creep rate of HAZ in comparison to the weld and base metal. Compared to base metal, shielded metal arc weld (SMAW) and activated tungsten inert gas (A-TIG) weld of the P9 steel weld joints exhibited better resistance to creep and displayed higher activation energy due to their coarser prior austenite grain size. A-TIG HAZ exhibited superior creep properties compared to the SMAW and TIG HAZ due to the presence of higher number density of precipitates.